Development and Validation of a UPLC–ESI(-)–MS/MS Methodology for the Simultaneous Quantification of Hesperidin, Naringin, and their Aglycones in Chicken Tissue Samples. (29th January 2020) - Baira, Eirini; Dagla, Ioanna; Siapi, Eleni; Zoumpoulakis, Panagiotis; Tsarbopoulos, Anthony; Simitzis, Panagiotis; Goliomytis, Michael; Deligeorgis, Stelios G; Skaltsounis, Alexios-Leandros; Gikas, Evagelos
Abstract: Background: The dietary supplementation of livestock with antioxidants to improve the meat quality represents an active research area of high commercial impact. In order to investigate the optimal dosing, analytical methodologies need to be developed in various tissues to evaluate which concentration does remain in the tissue. Objective: We aimed to develop and validate a sensitive and specific methodology for the simultaneous quantitative determination of hesperidin, naringin, hesperetin, and naringenin in chicken tissue samples employing ultra-performance LC–tandem MS. Methods: Lipid extraction using cold chloroform was performed followed by protein precipitation by cold acetone. Chromatography was performed on a C18 column using a ternary gradient of water, acetonitrile, and isopropanol–acetonitrile–acetone (58+40+2, v/v) as the mobile phase. Detection was performed by electrospray ionization in negative ion mode with the selected reaction monitoring technique. Results: Calibration plots exhibited good linearity ( r 2 > 0.99) over the concentration range from 0.125 to 25 μg/g tissue for the four analytes, and the lower LOQ for the four analytes was 0.125 μg/g tissue. The repeatability as percent relative SD and precision as percent accuracy were <20 and >80%, respectively. Conclusions: The developed methodology was applied for the quantitative determination of hesperidin, naringin, hesperetin, and naringenin in tissue samples after dietary supplementation with 1.5 g/kg hesperidin and 1.5 g/kg naringin in Ross 308 broiler chickens. Highlights: This is the first methodology to access naringin, naringenin, hesperidin, and hesperetin in chicken tissue. It involved simple sample preparation, and the mass spectrometry based detection ensures high specificity and sensitivity.